2012
DOI: 10.1007/s13181-011-0204-0
|View full text |Cite
|
Sign up to set email alerts
|

Mortality Predictors of Snake Bite Envenomation in Southern India—A Ten-Year Retrospective Audit of 533 Patients

Abstract: Snake bite incidence is highest in Asia and sub-Saharan Africa. This retrospective audit of 533 adult patients, who had presented to the Emergency Department, collates clinical features, effect of pharmacologic interventions and the risk factors that influence morbidity and mortality. Dual toxicity, neurological and haematological, was observed in 30.4% of patients. Laboratory evidence of haematotoxicity was demonstrated in 314 (58.9%) and 40% demonstrated clinical evidence of bleeding. However, 7.3% of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 6 publications
3
37
1
1
Order By: Relevance
“…AKI is a strong predictor of mortality among the in-hospital patients with snake bite[22,34]. Mortality of 9.1% was observed in our study.…”
Section: Discussionsupporting
confidence: 51%
“…AKI is a strong predictor of mortality among the in-hospital patients with snake bite[22,34]. Mortality of 9.1% was observed in our study.…”
Section: Discussionsupporting
confidence: 51%
“…[16,18,19] One study from southern India reported acute kidney injury in 28% of snakebite patients, with a significant association with mortality. [23] …”
Section: Discussionmentioning
confidence: 99%
“…The envenoming snake species is highly likely to influence the clinical presentation and outcome, but many studies have considered together bites from different snake species [9], [14], [26], [37], [94], [156][158]. Such differences are perhaps unavoidable as confirming the identity of the envenoming snake is often difficult.…”
Section: Clinical Manifestationsmentioning
confidence: 99%